The Illocutionary Acts in Melati and Isabel Wijsen’s Ted Talk - Ni Wayan Suastini; I Wayan Sidha Karya; Ni Nyoman, Indrayani Erlina Saputri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
With some kind of purpose in mind, the Illocutionary Act learns about the utterance performed. The goal of this study is to resolve the research problems consisting of: (1) What are the types of illocutionary acts found in Ted Talk by Melati and Isabel Wijsen; and (2) What is the role of the illocutionary act used by Ted Talk by Melati and Isabel Wijsen? The data in this analysis were analyzed by Searle (1979) and Leech (1983) respectively, applying the theory of illocutionary forms and functions. 64 statements containing types of illocutionary actions, such as: assertive, directive, commissive and expressive, are shown as the outcome of this study. The most utterances delivered by Melati and Isabel Wijsen in their Ted Talk are assertive, seen in 50 utterances or (78,13 percent). Commissive, directive and expressive are accompanied by the occurrence of eight utterances (12,50 percent), four utterances (6,25 percent), and 2 utterances (3,13 percent). In Melati and Isabel Wijsen's speech, the declarative is not found since the act involves particular circumstances. Moreover, only 3 roles of an illocutionary act were included in the study. It's competitive, fun, and collaborative. Collaborative was the function of illocutionary actions found most in this group. Keywords: Illocutionary Acts, Melati and Isabel Wijsen, Ted Talk